2012
DOI: 10.5511/plantbiotechnology.12.0106a
|View full text |Cite
|
Sign up to set email alerts
|

Development of an efficient mutagenesis technique using ion beams: Toward more controlled mutation breeding

Abstract: Ion beams have been used as a mutagen to improve the e ciency of plant mutation breeding. Mutation breeding is sometimes perceived as a random process. In this review, we describe our recent progress in developing a more e cient mutagenesis technique using ion beam irradiation combined with sucrose pretreatment or subsequent reirradiation. To shorten the time required for breeding new cultivars of cyclamen, we identi ed anthocyanin biosynthesis genes and examined the e ectiveness of PCR screening of irradiated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 22 publications
1
10
0
1
Order By: Relevance
“…For example, a pretreatment with sucrose, which upregulates the expression of anthocyanin biosynthesis genes, increases the number of flower-color mutants generated by carbon beam irradiation in petunia, although the frequency of chlorophyll mutations is almost unchanged [39]. Therefore, modulating the gene expression pattern may lead to increased controlled mutation, although the responsible mechanism will need to clarified [40].…”
Section: Effects Of Plant Tissue Type and Conditionmentioning
confidence: 99%
“…For example, a pretreatment with sucrose, which upregulates the expression of anthocyanin biosynthesis genes, increases the number of flower-color mutants generated by carbon beam irradiation in petunia, although the frequency of chlorophyll mutations is almost unchanged [39]. Therefore, modulating the gene expression pattern may lead to increased controlled mutation, although the responsible mechanism will need to clarified [40].…”
Section: Effects Of Plant Tissue Type and Conditionmentioning
confidence: 99%
“…The accumulated evidence suggests that ion beams efficiently induce mutations (Tanaka et al 2010;Hase et al 2012). Analyses of ionbeam irradiated mutants in higher plants showed that half of the mutants possessed large DNA alterations, whereas the rest had point-like mutations.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, gamma-ray irradiation has been the main treatment used in various plants, particularly ornamental plants such as orchids (Kikuchi, 2000), Anthurium (Puchooa, 2005), chrysanthemum (Kumar et al, 2012;Yamaguchi et al, 2008), and Paphiopedilum (Luan et al, 2012), for over 80 years. Recently, irradiation with ion beams, which are different from gamma-ray in that they are generated by accelerators and has specific mass and charge according to types of ions, has been proven to be very effective in mutation breeding in terms of biological effectiveness, mutation frequency, and range of mutation spectrum compared with gamma ray (Hase et al, 2012). New varieties in diverse crops including rice, verbena, carnation, and chrysanthemum have been developed using heavy-ion beams (Kanaya et al, 2008;Nagatomi, 2003;Okamura et al, 2003;Tanaka et al, 2010).…”
Section: Introductionmentioning
confidence: 99%